Study on the equivalent plastic hinge length of superimposed RC shear walls with embedded bracings. (May 2023) - Guo, Shengqi; Wang, Mengfu
Abstract: The equivalent plastic hinge length of RC shear wall is often regarded as an important index to be studied in the framework of performance-based seismic design, for which a series of evaluation formulae have been widely proposed. However, existing equivalent plastic hinge length calculation formulae are proposed for cast-in-place RC shear walls, while that for superimposed RC shear walls with embedded bracings (SRCXSWs) still needs to be further studied. With an attempt to achieve this goal, a series of research including finite element analysis and theoretical derivation are conducted in this research. Based on the analysis of crack development and failure modes for SRCXSW, the relationship between the ultimate deformation and the equivalent plastic hinge length is established through the theoretical derivation, then 51 finite element models with 10 parameters are analyzed by OpenSEES to summarize the influence modes of different parameters on the equivalent plastic hinge length. Finally, the equivalent plastic hinge length calculation formulae for SRCXSWs are proposed and verified by the numerical and experimental results. The research results illustrate that there exists a function relation between the ultimate deformation and the equivalent plastic hinge length, and decreasing the ratio of deformation caused by shear effect to top deformation or increasing the compressive strain properties of concrete by parameter assignment will be more conducive to the formation and development of the plastic hinge zone of SRCXSWs. The existing formulae cannot effectively estimate the equivalent plastic hinge length of SRCXSWs, while the proposed formulae are suitable for predicting the equivalent plastic hinge length of SRCXSWs.